1982
DOI: 10.1590/1809-43921982123s007
|View full text |Cite
|
Sign up to set email alerts
|

Composição isotópica da água de chuva e da água do solo em floresta amazônica do tipo terra firme, região de Manaus

Abstract: 0 aspecto abordado trata da observac;:ao dos conteudos isot6picos da agua de chuva e relac;:6es com as suas respectivas repartic;:oes em uma floresta amaz6nica do tipo terra firme. Pretende-se obter as bases para a realizac;:ao e continuidade de novos experimentos, utilizando-se da hidrologia isot6pica. MATERIAL E METODO0 trabalho foi realizado em area experimental da Bacia Modelo, pr6xima ao km 14 de estrada ZF-2.As coletas da agua proveniente das chuvas eram feitas semanalmente atraves de tres pluvi6metros l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
5

Year Published

1991
1991
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 6 publications
(6 reference statements)
1
3
0
5
Order By: Relevance
“…The close relationship between soil water content at 25 cm and recent shortterm rainfall supports the findings of Leopoldo et al (1982), who reported rapid infiltration and residence times of c. one week in this part of the profile at a similar site near Manaus. The good agreement of deeper soil MVFs with recent short-term rainfall patterns is more surprising in the light of the conclusion by Leopoldo et al (1982) that residence times at these depths are in the order of 2-4 weeks, and it suggests that drainage from individual storms, perhaps via the macropore system (Nortcliff & Thornes 1981), may be more rapid than initially supposed.…”
Section: Soil Water Availabilitysupporting
confidence: 86%
See 1 more Smart Citation
“…The close relationship between soil water content at 25 cm and recent shortterm rainfall supports the findings of Leopoldo et al (1982), who reported rapid infiltration and residence times of c. one week in this part of the profile at a similar site near Manaus. The good agreement of deeper soil MVFs with recent short-term rainfall patterns is more surprising in the light of the conclusion by Leopoldo et al (1982) that residence times at these depths are in the order of 2-4 weeks, and it suggests that drainage from individual storms, perhaps via the macropore system (Nortcliff & Thornes 1981), may be more rapid than initially supposed.…”
Section: Soil Water Availabilitysupporting
confidence: 86%
“…The good agreement of deeper soil MVFs with recent short-term rainfall patterns is more surprising in the light of the conclusion by Leopoldo et al (1982) that residence times at these depths are in the order of 2-4 weeks, and it suggests that drainage from individual storms, perhaps via the macropore system (Nortcliff & Thornes 1981), may be more rapid than initially supposed.…”
Section: Soil Water Availabilitymentioning
confidence: 94%
“…Essa equação estimou que valores de precipitações inferiores a 6,2 mm h -1 são desviados para os troncos, retidos e devolvidos à atmosfera por evaporação e não alcançam a superfície do terreno. O valor da capacidade de retenção da chuva pelos troncos encontrado neste trabalho está dentro do intervalo obtido em outros estudos como os 8,5 mm de Leopoldo (1981) na Amazônia central, de Huber e Oyarzún (1983 e 1992) que calcularam 6,0 e 5,1 mm, respectivamente em Pinus Radiata, no Chile. Assim como o encontrado para mata ciliar em São Paulo por Lima (1998) e, Lima e Leopoldo (1999) que obtiveram o menor valor de 4,2 mm.…”
Section: Escoamento Pelo Troncounclassified
“…O importante papel da evapotranspiração se reflete na variabilidade isotópica da precipitação, que tem como característica principal, um efeito sazonal com valores empobrecidos durante o verão, associado à atuação da Zona de Convergência Intertropical (ZCIT), e valores enriquecidos durante o inverno (SALATI et al 1979, LEOPOLDO et al 1982, MATSUI et al 1983.…”
Section: Estudos Isotópicos Sobre a Precipitação No Brasilunclassified